"Its Own Kind of Torture": Denial, Acknowledgment, and the Debate About Force Feeding at Guantánamo Bay1. Issue 1 (11th December 2017) - Del Rosso, Jared
Abstract : Social science research has revealed how U.S. political and media elites, as well as U.S. citizens, downplayed and denied allegations of torture during the country's wars in Afghanistan and Iraq. This research effectively applies and extends Stanley Cohen's (2001 ) typology of the rhetoric of denial. We lack, however, a typology of the rhetoric of acknowledgment. In this article, I synthesize studies of discourse of torture to develop just such a typology. I propose three rhetorical forms of acknowledgment, which parallel Cohen's forms of denial. Literal or factual acknowledgment includes claims to convince audiences that alleged incidents indeed occurred. Interpretive acknowledgment consists of claims to affirm that those allegations constitute serious human rights violations, such as cruel, inhuman, or degrading treatment or torture. Implicatory acknowledgment includes efforts to delegitimize torture. I then illustrate the use of the rhetoric of acknowledgment through a qualitative content analysis of newspaper coverage of force feeding at the United States' detention center at Guantánamo Bay, Cuba. This case allows me to extend our understanding of the rhetoric of denial and acknowledgment by revealing ways in which discourse around force feeding deviates from that around the United States' use of "enhanced interrogation" and torture.